1994
DOI: 10.1161/01.hyp.23.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of blood pressure in community-dwelling older adults. The Cardiovascular Health Study. Cardiovascular Health Study (CHS) Collaborative Research Group.

Abstract: Although elevated blood pressure is an important predictor of cardiovascular disease and stroke in the elderly, little information exists on the distribution and risk factor correlates of blood pressure in this group. As part of the Cardiovascular Health Study, a population-based cohort study of 5201 men and women aged 65 to 101 years, we investigated correlates of systolic and diastolic blood pressure. Multiple regression analyses were conducted for all participants and a subgroup of 2482 without coronary hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(32 citation statements)
references
References 37 publications
4
28
0
Order By: Relevance
“…237 In the Cardiovascular Health Study, the severity of carotid artery stenosis was greater in current smokers than in former smokers, and there was a significant relationship between the severity of carotid stenosis and pack-years of exposure to tobacco. 239 The RRs of finding Ͼ60% carotid stenosis were 1.5 and 3.9 among cigarette smokers with cerebral ischemia in the NOMASS and the BCID (Berlin Cerebral Ischemia Databank) studies, respectively. 258 The relationship between cholesterol and ischemic stroke is not as evident as that between cholesterol and MI, and findings from population-based studies are inconsistent.…”
Section: Medical Therapy For Patients With Atherosclerotic Disease Ofmentioning
confidence: 95%
“…237 In the Cardiovascular Health Study, the severity of carotid artery stenosis was greater in current smokers than in former smokers, and there was a significant relationship between the severity of carotid stenosis and pack-years of exposure to tobacco. 239 The RRs of finding Ͼ60% carotid stenosis were 1.5 and 3.9 among cigarette smokers with cerebral ischemia in the NOMASS and the BCID (Berlin Cerebral Ischemia Databank) studies, respectively. 258 The relationship between cholesterol and ischemic stroke is not as evident as that between cholesterol and MI, and findings from population-based studies are inconsistent.…”
Section: Medical Therapy For Patients With Atherosclerotic Disease Ofmentioning
confidence: 95%
“…DBP has been shown to decrease in old age whereas SBP continues to rise leading to an increasing prevalence of isolated systolic hypertension and an increasing PP. 5,6,[8][9][10]12,13 The blood pressure changes in old age can be attributed to stiffening of large, central, arteries, encompassing vessel wall changes such as increased amounts of collagen, decreased content and increased destruction of the elastic protein elastin, calcification and possibly also to alterations in vascular smooth muscle tone. 14,15 Hypertension is a threat to life at all ages and both sexes, it is one of the leading cardiovascular disorders and important risk factor for coronary artery diseases, cerebrovascular diseases and cardiac failure in elderly patient.…”
Section: -11mentioning
confidence: 99%
“…Longitudinal and cross-sectional studies have shown that systolic blood pressure increases and diastolic pressure may decrease with advancing age in Western societies [1][2][3][4][5][6] , while in primitive, isolated populations blood pressure does not change after childhood or adolescence [5] . On the other hand, some longitudinal and cross-sectional studies have indicated that on their own systolic blood pressure or diastolic blood pressure, or both systolic blood pressure and diastolic blood pressure can be low or decrease in old age [1,3,[7][8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%